Double Wronskian solutions to the (2+1)-dimensional Broer–Kaup–Kupershmidt equation. (July 2020) - Tang, Yaning; Yuen, Manwai; Zhang, Lijun
Abstract: In this paper double Wronskian solutions to the Broer–Kaup–Kupershmidt (BKK) equation are investigated by using of Hirota method and binary bell polynomials. By introducing different auxiliary functions, the bilinear equations for the BKK equation in different forms are obtained respectively. Based on the distinct Hirota bilinear equations, two groups of double Wronskian solutions to the BKK equation are constructed.